Efektifitas Media Sosial Sebagai Media Pengajaran Iman Kristen (Jurnal Pendidikan Agama dan Teologi, 2023)
Social media has become an important part of modern human life and has influenced various aspects of life, including religion. In the context of the Christian faith, social media can be used as a medium for teaching and spreading religious messages. The purpose of this research is to explore the effectiveness of social media as a medium for teaching Christian faith. This research was conducted by surveying social media users who follow Christian accounts and are active in participating in online religious activities. Respondents were given a questionnaire to assess their experience in using social media as a medium for teaching Christian faith, including the type of content they liked and their level of involvement in online religious activities. The results of this study indicate that social media can be effective as a medium for teaching Christian faith. Respondents indicated that they had high levels of involvement in online religious activities and that they preferred to obtain religious information and teaching through social media rather than traditional sources such as books or seminars. The types of content most liked by respondents were quotes from the Bible, teaching videos, and personal religious experiences. However, this research also shows that the effectiveness of social media as a medium for teaching Christian faith can be influenced by various factors, such as the quality of the content and the user's trust in information sources. Therefore, there needs to be continuous monitoring and evaluation of content posted on social media so that the religious messages conveyed can be well received by social media users.